2016
DOI: 10.1108/tlo-09-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

Organizational learning through transformational leadership

Abstract: Purpose The transformation of firms from resource-based-view to knowledge-based-view has extended the importance of organizational learning. Thus, this study aims to develop an organizational learning model through transformational leadership with indirect effect of knowledge management process capability and interactive role of knowledge-intensive culture. Design/methodology/approach Different statistical analyses were done to check the direct, indirect and interactive effects on 204 valid responses. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 67 publications
2
75
1
3
Order By: Relevance
“…Findings related to the second main hypothesis indicate that transformational leadership has a significant effect on organizational learning capability. This finding aligns with other previous studies (Radzi et al, 2013;Alsabbagh and Alkhalil, 2016;Imran et al, 2016) that demonstrated the importance of transformational leaders in enhancing and supporting organizational learning capabilities. This tends to support the assumption that a transformational leadership style examines, alters and guides systems, building them in ways that share and distribute knowledge through organizational learning.…”
Section: Second Main Hypothesissupporting
confidence: 93%
“…Findings related to the second main hypothesis indicate that transformational leadership has a significant effect on organizational learning capability. This finding aligns with other previous studies (Radzi et al, 2013;Alsabbagh and Alkhalil, 2016;Imran et al, 2016) that demonstrated the importance of transformational leaders in enhancing and supporting organizational learning capabilities. This tends to support the assumption that a transformational leadership style examines, alters and guides systems, building them in ways that share and distribute knowledge through organizational learning.…”
Section: Second Main Hypothesissupporting
confidence: 93%
“…Theoretical grounds of KM suggest that OL is one of its outcomes [26] and leads to develop readiness for change in organizations [114,115].…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Organizational learning capability is defined as the set of organizational abilities, attributes, skills that allow organization to process knowledge and experiences, transfer and store them in ways that make them available for employees (Imran et al, 2016). This can be measured in terms of managerial commitment, system perspective, openness and experimentation and knowledge transfer and integration.…”
Section: Organizational Learning Capability (Mediating Variable)mentioning
confidence: 99%
“…Therefore, the fourth null sub hypothesis is rejected and the alternative is accepted. (Radzi et al, 2013;Alsabbagh and Alkhalil, 2016;Imran et al, 2016) that demonstrated the importance of transformational leaders in enhancing and supporting organizational learning capabilities. This tends to support the assumption that a transformational leadership style examines, alters and guides systems, building them in ways that share and distribute knowledge through organizational learning.…”
Section: Hypotheses Testingmentioning
confidence: 99%